Potential of textile-dye extract as the sensitizer in dye-sensitized solar cells - Muhamad Yudatama Perdana; Pregia Anugratama; Nur Habib Rizki Saputro; Fahru Nurosyid (Universitas Sebelas Maret, 2022)
A dye-sensitized solar cell (DSSC) is a device for converting photons from sunlight into electrical energy. In a DSSC, an important role is played by the dye sensitizer, which absorbs light and injects excitation electrons into the conduction band of a semiconductor oxide. As the sensitizer, complex ruthenium-based dyes provide high conversion efficiency but are expensive and scarce. As alternatives to Ru-based dyes, natural ones extracted from plants are environmentally friendly, inexpensive, and abundant. However, in DSSCs natural dyes are yet to offer higher conversion efficiency than that of complex Ru-based dyes, given low absorption in the visible range and low stability. High-purity textile dyes have been investigated as sensitizers in DSSCs, and dispersive azo dyes for textiles have been purified successfully by column chromatography, with a minimum purity of 97.3%. As such, textile-dye extract could be used as a dye in a DSSC by purifying the former using column chromatography. This article describes research on (i) DSSC fabrication and characterization, (ii) column chromatography for purifying dispersive azo dyes, (iii) the absorbance of several types of textile dye, (iv) the characteristics of the textile dye Remazol Red RB-133, and (v) the performance of a DSSC based on that dye.